Adaptation of Several New Superior Varieties of Rice under the Shade of Coconut - Sution Sution; Tietyk Kartinaty (UNIVED Press, Dehasen University Bengkulu, 2022)
One of the efforts to increase rice production can be done by utilizing land between plantation crops. However, the obstacle faced by intercrops among plantation crops is the low light intensity received by plants. The solution that can be done is to use new high yielding varieties that are shade tolerant. This study aims to produce several varieties of rice that have good adaptation to growth and yield in shaded conditions under coconut stands. The study used a Randomized Block Design (RBD) which consisted of 7 treatment varieties, namely Rindang 1, Rindang 2, Inpago 8, Inpago 9, Situ Bagendit, Inpari 32 and Jeliteng, then repeated 4 times. The results showed that the Rindang 1, Rindang 2, Inpago 8 and Inpago 9 varieties were higher than the high yielding varieties between 15.16-52.04 cm. The number of contents and the number of grain per panicle was highest in the Inpago 8 and Inpago 9 varieties. The highest 1000 grain weight was in the Rindang 2 variety, which was 31.09 g. VUB adaptation test under the shade of coconut varieties Inpago 8 and Inpago 9 productivity above 4 tons-1, while the varieties Rindang 1 and Rindang 2 productivity 3.7 tons-1 and 3.9 tons-1